Linear Complementary Pairs of Multi-twisted Codes and their Characterizations - Rubayya,; Ali, K. S. Mansoor; Datt, M. Sumanth (Communications in Mathematics and Applications, 2022)
The linear complementary pairs (LCP) of codes is studied mainly due to their application in cryptography. It is used in the protection against physical attacks such as the side channel and fault injection. In this paper, we study the LCP of codes which belong to the class of multi-twisted codes. We give characterizations for the multi-twisted LCP of codes via their constituents and in terms of the generator polynomial of the code
Keywords: Linear complementary pair; Multi-twisted code; Finite field; Constituents